2018
DOI: 10.1136/bmjopen-2017-020677
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in glycaemic control, cardiovascular disease risk factors and treatment in patients with type 2 diabetes: a cross-sectional study from the Australian National Diabetes Audit

Abstract: ObjectiveTo compare the glycaemic control and cardiovascular risk factor profiles of younger and older patients with type 2 diabetes. Cross-sectional analysis of data from the 2015 Australian National Diabetes Audit was undertaken.MethodsData were obtained from adults with type 2 diabetes presenting to Australian secondary/tertiary diabetes centres. Logistic regression examined associations with glycated haemoglobin A1c (HbA1c) >7% (53 mmol/mol) and cardiovascular risk factors.ResultsData from 3492 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 32 publications
(33 reference statements)
4
26
1
1
Order By: Relevance
“…In stratified analysis, we reanalyzed the data for gender and age groups, and we showed that DM only in females and patients younger than 65 years increased the risk of death. Previous observations confirmed the age and gender differences in glycemic control and treatment responses in diabetic patients [26][27][28][29][30]. According to the evidence, women with DM are less likely to reach the ideal level of hemoglobin A1c (HbA1c) compared with men [26,27,30].…”
Section: Table 4 Predicting Factors For Death Of the Covid-19 In Patimentioning
confidence: 68%
See 1 more Smart Citation
“…In stratified analysis, we reanalyzed the data for gender and age groups, and we showed that DM only in females and patients younger than 65 years increased the risk of death. Previous observations confirmed the age and gender differences in glycemic control and treatment responses in diabetic patients [26][27][28][29][30]. According to the evidence, women with DM are less likely to reach the ideal level of hemoglobin A1c (HbA1c) compared with men [26,27,30].…”
Section: Table 4 Predicting Factors For Death Of the Covid-19 In Patimentioning
confidence: 68%
“…The risk of all-cause mortality was higher in females with DM. Moreover, surveys showed that younger adults have poorer glycemic control compared to older diabetic patients [28,29]. These issues are of great importance in interpreting the findings of epidemiological studies.…”
Section: Table 4 Predicting Factors For Death Of the Covid-19 In Patimentioning
confidence: 99%
“…In strati ed analysis, we reanalyzed the data for gender and age groups, and we showed that DM only in females and patients younger than 65 years increased the risk of death. Previous observations con rmed the age and gender differences in glycemic control and treatment responses in diabetic patients [26][27][28][29][30]. According to the evidence, women with DM are less likely to reach the ideal level of hemoglobin A1c (HbA1c) compared with men [26,27,30].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of all-cause mortality was higher in females with DM. Moreover, surveys showed that younger adults have poorer glycemic control compared to older diabetic patients [28,29]. These issues are of great importance in interpreting the ndings of epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Los años de diagnóstico influyeron de forma inversa en el autocuidado. Esto difiere con otro estudio 55 , en el que el bajo control glucémico en personas se asocia con quienes tienen menos de seis años con la enfermedad. Lo anterior indica que la evolución de la diabetes es una condición que puede limitar el autocuidado y asociarse al descontrol glucémico.…”
Section: Discussionunclassified